(untitled) (Revista Brasileira Multidisciplinar, 2024)
Diabetes mellitus is a chronic metabolic syndrome characterized by the insistent rising of blood sugar levels. Pharmacologic therapy includes insulin administration and oral hypoglycemic medications which have side effects such as hypoglycemia and gastrointestinal disorders and are not always effective in preventing and treating diabetes complications. The search for natural alternatives is a promising strategy in the treatment of chronic diseases. Brown macroalgae of the genus Sargassum has shown a range of secondary metabolites with several biological activities, such as anti-inflammatory, antitumoral, antimicrobial, neuroprotective, hypolipidemic and hypoglycemic activity. Therefore the aim of this work was to carry out a literature review of the antidiabetic activity of Sargassum spp. Either extracts or isolated compounds/fractions of compounds of these algae could reduce diabetes symptoms through various mechanisms, such as in vitro inhibition of the key enzymes in polysaccharides breakage, α-amylase and α-glucosidase, and the reduction of insulin resistance, providing the amelioration of the hyperglycemic condition. Thus Sargassum spp and their bioactive compounds have a great potential in the treatment of diabetes and prevention of the micro and macrovascular complications resulting from sustained hyperglycemic state.